Assessing biomarkers of exposure to carcinogens associated with combustible cigarettes, electronic cigarettes, and heated tobacco products: a systematic review and meta-analysis - Cao, Yue; Zhang, Lin; Yang, Mengqi; Li, Jiaxuan; Chen, Xi; Zheng, Fangzhen; Zhang, Jianqiang; Xu, Xiao; Liu, Xiaona (Frontiers in Pharmacology, 2025)
IntroductionThere is growing global concern about the emissions of harmful and potentially harmful constituents (HPHCs) associated with electronic cigarette (EC) and heated tobacco product (HTP) use. This systematic review evaluates biomarkers of exposure (BoEs) for carcinogens in individuals who switched from combustible cigarettes (CCs) to either ECs or HTPs.MethodsA literature search was performed across PubMed, Ovid, and Web of Science for randomized controlled trials (RCTs) published from January 2013 to March 2024. Data synthesis was conducted using a random-effects meta-analysis, calculating ratios of means (RoMs) to compare biomarker concentrations among individuals who completely switched to ECs or HTPs, those who abstained from smoking, and those who continued smoking CCs.ResultsOur analysis included 18 RCTs, examining 14 BoEs for FDA-identified carcinogenic HPHCs. Compared to continual CC smokers, individuals who completely switched to ECs demonstrated significantly lower exposure to eight carcinogens (i.e., 2-AN, 4-ABP, HEMA, MHBMA, NNAL, NNN, S-PMA, o-Tol; RoMs range: 0.031–0.461). Those who fully transitioned to HTPs showed significantly lower exposure to 12 carcinogens (i.e., 1-AN, 2-AN, 3-HMPMA, 3-OH-B [a]P, 4-ABP, CEMA, HEMA, MHBMA, NNAL, NNN, S-PMA, o-Tol; RoMs range: 0.054–0.527). No statistically significant differences in carcinogenic exposures were observed when comparing smoking cessation, or full switching to ECs or HTPs for all evaluated BoEs to continuous CC smoking, except for 3-HMPMA, CEMA, and NNN.ConclusionIndividuals who completely switched from CCs to ECs or HTPs had significantly lower exposure to numerous carcinogenic HPHCs, with the degree of reduction for some toxicants potentially approaching those of smoking abstainers. However, these findings require careful interpretation, as the evidence is predominantly derived from short-term trials (5–7 days). Further research should explore the long-term health impacts of residual nicotine and tobacco-specific toxicant exposures among these switchers.